Transcriptome and proteomic analyses reveal multiple differences associated with chloroplast development in the spaceflight-induced wheat albino mutant mta. - Kui Shi; Jiayu Gu; Huijun Guo; Linshu Zhao; Yongdun Xie; Hongchun Xiong; Junhui Li; Shirong Zhao; Xiyun Song; Luxiang Liu (PLoS ONE, 2017)
Chloroplast development is an integral part of plant survival and growth, and occurs in parallel with chlorophyll biosynthesis. However, little is known about the mechanisms underlying chloroplast development in hexaploid wheat. Here, we obtained a spaceflight-induced wheat albino mutant mta. Chloroplast ultra-structural observation showed that chloroplasts of mta exhibit abnormal morphology and distribution compared to wild type. Photosynthetic pigments content was also significantly decreased in mta. Transcriptome and chloroplast proteome profiling of mta and wild type were done to identify differentially expressed genes (DEGs) and proteins (DEPs), respectively. In total 4,588 DEGs including 1,980 up- and 2,608 down-regulated, and 48 chloroplast DEPs including 15 up- and 33 down-regulated were identified in mta. Classification of DEGs revealed that most were involved in chloroplast development, chlorophyll biosynthesis, or photosynthesis. Besides, transcription factors such as PIF3, GLK and MYB which might participate in those pathways were also identified. The correlation analysis between DEGs and DEPs revealed that the transcript-to-protein in abundance was functioned into photosynthesis and chloroplast relevant groups. Real time qPCR analysis validated that the expression level of genes encoding photosynthetic proteins was significantly decreased in mta. Together, our results suggest that the molecular mechanism for albino leaf color formation in mta is a thoroughly regulated and complicated process. The combined analysis of transcriptome and proteome afford comprehensive information for further research on chloroplast development mechanism in wheat. And spaceflight provides a potential means for mutagenesis in crop breeding.